Collinson, Yvonne Mary Pynn. Interview about growing up in Petty Harbour. - Barrett, Terra (2014)
Interview with Yvonne Mary Pynn Collinson (Stack) focuses on growing up in Petty Harbour, children's games and activities, community events, and family stories.